Tellurium-copper alloy and preparation method and application thereof

By regulating the content of Te, P, Y, and Ce in tellurium copper alloy and the process treatment, an optimized Cu2Te phase structure is formed, which solves the gas leakage problem caused by the sealed structure of the high-voltage DC relay, significantly reduces the helium leakage detection defect rate, and improves the multiple properties of the material.

CN119753419APending Publication Date: 2025-04-04JINTIAN COPPER GROUP CORP NINGBO
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411949491.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The sealed structure of existing high-voltage DC relays is prone to damage, resulting in protective gas leakage, affecting service life and safety, and the helium leakage detection rate is high.

Method used

By regulating the content of Te, P, Y, and Ce in the tellurium copper alloy, Cu2Te phase is formed, and the structure and performance of the alloy are optimized, and its conductivity, arc ablation resistance and airtightness are improved.

Benefits of technology

It significantly reduces the helium leakage detection defect rate of high-voltage DC relays to be less than 50ppm, improves the conductivity, tensile strength and elongation of the material, while ensuring arc ablation resistance and airtightness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753419A_ABST
    Figure CN119753419A_ABST
Patent Text Reader

Abstract

The tellurium-copper alloy comprises Cu, Te, doping elements and inevitable impurities, the total mass percentage of all the elements is 100%, the Te accounts for 0.2-0.4 wt%, the doping elements comprise 0.002-0.006 wt% of P and 0.02-0.06 wt% of X, X is Y and / or Ce, and the inevitable impurities comprise Cu, Te, doping elements and inevitable impurities. The structure of the tellurium-copper alloy comprises Cu2Te phases, and the number distribution of the Cu2Te phases is 7000 to 10000 / mm < 2 >. The tellurium-copper alloy has better conductivity, arc ablation resistance and processability, is compact and low-oxygen, and has better airtight performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of copper alloy technology, specifically relating to a tellurium copper alloy, its preparation method, and its application. Background Technology

[0002] Tellurium copper alloys possess characteristics such as high conductivity, ease of machining, arc resistance, and corrosion resistance, making them suitable for applications in connectors, plasma cutting nozzles, and relay contacts. In recent years, with the increasing popularity of electric vehicles, the application of high-voltage DC relays has also expanded. Currently, mainstream electric vehicles use a 400V voltage platform. However, with rising consumer demand for faster charging speeds and longer driving ranges, some electric vehicle manufacturers have begun to develop 800V or even higher voltage platforms.

[0003] High-voltage DC relays are core electrical components specifically designed for controlling high-voltage DC circuits in electric vehicles. Higher voltage platforms place greater demands on the withstand voltage, current-carrying capacity, arc-extinguishing performance, and contact resistance of high-voltage DC relays. Currently, to achieve effective arc cooling and reduce contact erosion, high-voltage DC relays employ two main methods: first, a sealed structure using hydrogen, nitrogen, or a mixture of both gases; and second, the use of tellurium copper alloy, which resists arc erosion, as the contact material. The protective gas cools the arc, and its reducing properties also protect the contact material. If the sealed structure of a high-voltage DC relay is compromised, and the protective gas leaks, its service life and safety will inevitably be affected. Therefore, to ensure the airtightness of high-voltage DC relays, manufacturers must perform helium leak testing.

[0004] The invention patent application with publication number CN110284024A discloses a method for preparing tellurium copper alloy material, including the following steps: (1) Smelting: Cathode copper is added to a smelting furnace and heated to melt; after complete melting, phosphorus copper master alloy is added for deoxidation, and then tellurium copper master alloy is added. The furnace temperature is controlled at 1250℃~1260℃. After holding at the temperature and standing, rare earth elements are added. After complete melting, the furnace temperature is adjusted to 1200℃~1240℃ and water-cooled and cast into ingots; (2) Extrusion deformation processing is performed; (3) Pickling and hydraulic drawing are performed; (4) Polishing and length setting are performed to obtain the product; The elemental composition of the tellurium copper alloy material is as follows by weight percentage: Te 0.15~0.5%; R 0.08~0.12%; P 0.002~0.005%; Cu balance; R is at least one of the rare earth elements scandium or yttrium.

[0005] The invention patent application with publication number CN116083749A discloses a tellurium copper alloy strip, characterized in that: the mass percentage composition of the tellurium copper alloy is Te: 0.1~0.3wt%, P: 0.008~0.012wt%, RE: 0.01~0.05wt%, RE is selected from Ce and / or La, and the balance is copper and unavoidable impurities. Rare earth elements are added to the copper matrix, and their enrichment at grain boundaries refines the grains. The addition of Te strengthens the copper matrix with second-phase particles, preventing a decrease in the plasticity of the strip during high-rate processing. Ultimately, this tellurium copper alloy strip achieves a hardness of 90–120 HV1, tensile strength ≥280 MPa, elongation ≥15%, electrical conductivity ≥97% IACS, and high-temperature softening temperature ≥400℃. Under 90° bending conditions, the strip satisfies R / t≤1.0 in both the direction perpendicular to and parallel to the rolling direction.

[0006] However, the failure rate of helium leak detection in high-voltage DC relays made of tellurium copper alloy materials disclosed in the above-mentioned patent applications is generally higher than 100ppm, which greatly increases the production cost of manufacturers. The main reason is that the tellurium copper alloy used to prepare the static contacts has tiny pores, which leads to leakage. Summary of the Invention

[0007] This invention provides a tellurium-copper alloy, which has good electrical conductivity, resistance to arc erosion and processing performance, and is dense, low in oxygen, and has good airtightness.

[0008] This invention provides a tellurium copper alloy comprising Cu, Te, dopant elements and unavoidable impurities, wherein the total mass percentage of all elements is 100%, wherein Te: 0.2-0.4 wt%, and the dopant elements include P: 0.002-0.006 wt%, X: 0.02-0.06%, where X is Y and / or Ce;

[0009] The microstructure of the tellurium copper alloy includes a Cu2Te phase, with a quantity distribution of 7000-10000 phases / mm. 2 .

[0010] This invention obtains a copper alloy material with high conductivity, low oxygen content, resistance to arc erosion, and dense microstructure by controlling the content of Te, P, Y, and Ce in the alloy.

[0011] The Te content provided by this invention has a significant impact on the arc erosion resistance of tellurium copper alloys. Te has a low melting and boiling point, is almost insoluble in the copper matrix, and combines with Cu to form Cu₂Te. When tellurium copper alloy is used as a contact material, under the heat of an electric arc, Cu₂Te in the alloy decomposes, and the low-boiling-point, high-vapor-pressure Te rapidly vaporizes, absorbing heat from the alloy sample surface, cooling the arc, and playing a certain role in extinguishing the arc, thus preventing the arc from eroding the contact material. When the Te content is below 0.2 wt%, the improvement in the material's arc resistance is not significant; when the Te content is above 0.4 wt%, the increased Cu₂Te tends to accumulate at grain boundaries, leading to increased brittleness and a tendency for microcracks to form at high processing rates, which can cause leakage when used as a contact material for high-voltage DC relays. Therefore, when the Te content is 0.2-0.4 wt%, both the arc erosion resistance and the ability to undergo high processing rates can be guaranteed without cracking or airtightness risks.

[0012] The phosphorus (P) element provided in this invention has a significant impact on the oxygen content and density of tellurium copper alloys. During smelting, P can combine with oxygen in the melt, thereby purifying the melt. Additionally, P can reduce the gas content in the melt, preventing porosity during solidification into ingots, improving material density, and avoiding leakage when used as a contact material for high-voltage DC relays. When the P content is less than 0.002 wt%, the deoxygenation and degassing effects are poor, increasing the probability of leakage when used as a contact material for high-voltage DC relays. When the P content is greater than 0.006 wt%, the negative impact of P on conductivity increases, leading to increased temperature rise in electrical contacts when used as a contact material for high-voltage DC relays, thus affecting its safety and durability.

[0013] Rare earth elements Y or Ce have a significant impact on the purity, conductivity, and microstructure of tellurium copper alloys. On the one hand, rare earth elements Y and Ce are extremely reactive, with high electronegativity and strong chemical activity. They can form high-melting-point rare earth compounds with impurities such as oxygen, hydrogen, sulfur, phosphorus, lead, and bismuth. These compounds float to the surface of the melt, forming slag that is removed and purifies the melt, thereby improving the conductivity of the tellurium copper alloy. On the other hand, a small amount of high-melting-point rare earth compounds disperse in the melt, becoming heterogeneous nucleation sites. This increases the nucleation rate of crystallization, refines the alloy microstructure, and increases the number of grain boundaries, leading to greater resistance to dislocation movement. This improves the machinability of the tellurium copper alloy, reduces the generation of microcracks during processing, and lowers the probability of leakage in high-voltage DC relay contact materials. When the amount of Y or Ce or the sum of both is less than 0.02%, the purification and refining effect on tellurium copper alloy cannot be achieved; when the amount of Y or Ce or the sum of both is greater than 0.06%, the conductivity of tellurium copper alloy will be reduced.

[0014] Preferably, the average grain size of the tellurium copper alloy is 10-20 μm. Too small an average grain size will result in an excessive amount of Cu2Te phase per unit area, making it prone to microcracks during subsequent processing. Too large an average grain size will result in an insufficient amount of Cu2Te phase per unit area, affecting the material's arc resistance.

[0015] Preferably, the tellurium copper alloy has a conductivity >90% IACS, an oxygen content <10ppm, a tensile strength >230MPa, an elongation >25%, and an arc burn-off loss of less than 5mg after 500 cycles.

[0016] The present invention also provides a method for preparing the aforementioned tellurium copper alloy, wherein the process flow of the preparation method is as follows: batching and casting → hot extrusion → pickling → stretching → high temperature quenching → pickling → finished product stretching.

[0017] The ingredients are prepared according to the percentage of each component in the tellurium copper alloy.

[0018] The high-temperature quenching temperature is 620–780℃, and the holding time is 30–120 min.

[0019] Because the Cu2Te phase inside the matrix undergoes severe fragmentation after stretching, resulting in an excessive distribution of Cu2Te phase within the material, microcracks are easily generated during subsequent processing, which affects the airtightness and may lead to the failure of helium leak detection results. Therefore, this invention controls the high-temperature quenching temperature and holding time to appropriately aggregate the fragmented Cu2Te phase, reducing the amount of Cu2Te phase in the matrix and ensuring a suitable distribution of Cu2Te phase in the matrix, thereby reducing the risk of cracking without affecting the material's arc resistance.

[0020] Preferably, the cooling method for the high-temperature quenching is water cooling. This invention reduces the time the material spends at high temperatures by water cooling the billet to room temperature, thus preventing secondary recrystallization and avoiding uneven processing deformation due to uneven grain structure, which could lead to microcracks and affect airtightness.

[0021] Preferably, during the casting process, charcoal is used to cover the surface of the melt. The charcoal provided by this invention has reducing properties, which can prevent oxidation and gas absorption in the melt. More preferably, the thickness of the charcoal cover is 10-20 cm.

[0022] Preferably, electromagnetic stirring of the melt is employed during the casting process. The electromagnetic field acts on the alloy melt to create stirring and convection effects, which can inhibit the growth of dendrites in the melt. Some coarse dendrites are broken up by electromagnetic force and become new nucleation points, thereby increasing the equiaxed crystal ratio of the solidification structure of the billet, achieving the purpose of refining the structure, and improving the processing performance of the material.

[0023] Preferably, the average grain diameter of the ingot obtained by the batching and casting is less than 500 μm. This invention controls the grain size of the ingot, resulting in a more uniform microstructure and enabling the finished product to achieve an average grain size of 10-20 μm.

[0024] Preferably, the hot extrusion ratio is 200-800, the extrusion temperature is 650-900℃, and the hot extrusion residual amount accounts for 5-15% of the original length of the extruded ingot. This extrusion ratio and temperature can ensure the smooth processing of the ingot, while the material structure is fully refined.

[0025] This invention processes ingots into bars or wires through hot extrusion, facilitating further processing. However, in the later stages of hot extrusion, the metal flow is prone to become turbulent, resulting in tailing defects. Due to the discontinuity and small size of these tailing defects, they are difficult to identify with the naked eye. Conventional tailing operations cannot completely remove all tailing defects, which become the source of leakage in the contact material of high-voltage DC relays. This invention extends the length of the extrusion residue, i.e., provides a suitable residue control amount, to avoid turbulent metal flow and tailing defects, thereby avoiding the source of leakage.

[0026] Preferably, the stretching process involves a processing amount of 20-50%. This invention achieves uniform and fine tissue structure through a large-scale stretching process that breaks down the tissue.

[0027] Preferably, the stretching rate of the finished product is 5-15%.

[0028] The present invention also provides the application of the aforementioned tellurium copper alloy in a high-voltage DC relay, wherein the high-voltage DC relay has a helium leak detection failure rate of less than 50 ppm.

[0029] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0030] This invention improves the arc erosion resistance of copper telluride alloys by providing an appropriate amount of Te, while avoiding the accumulation of Cu2Te phase at grain boundaries due to excessive Te content, which increases the material's brittleness and causes microcracks during processing. Furthermore, this invention controls the distribution of the Cu2Te phase, minimizing the impact of microcracks on airtightness while ensuring good arc resistance. This invention also provides an appropriate amount of P element to reduce the gas content of the melt, thereby reducing porosity and improving airtightness, while avoiding the decrease in electrical conductivity caused by excessive P element. Finally, this invention provides an appropriate amount of X element to refine the alloy microstructure, improve the material's machinability, reduce microcrack formation, and increase airtightness. Attached Figure Description

[0031] Figure 1 A 100x metallographic photograph of the copper alloy prepared in Example 2;

[0032] Figure 2 This is a 500x metallographic photograph of the copper alloy obtained in Example 3. Detailed Implementation

[0033] The present invention will be further described in detail below with reference to the embodiments.

[0034] This invention provides four embodiments and four comparative examples.

[0035] Example 1

[0036] The tellurium copper alloy comprises the following components by mass percentage: Te: 0.25wt%, P: 0.004wt%, Y: 0.04%, with the balance being electrolytic copper.

[0037] 1) Batching, smelting and casting: The batching is carried out for smelting and casting. During the smelting and casting process, the surface of the melt is covered with charcoal with a thickness of 10cm, and ingots are produced by continuous casting.

[0038] 2) Hot extrusion: The heated ingot is extruded in a horizontal extrusion press to obtain a billet. The extrusion ratio is 220, the extrusion temperature is 670℃, and the residual pressure accounts for 10% of the original length of the extruded ingot.

[0039] 3) Pickling: The hot-extruded billet is pickled to remove the surface oxide scale.

[0040] 4) Stretching: Cold deformation of the extruded billet by 25% processing amount.

[0041] 5) High-temperature quenching: The stretched wire blank is subjected to high-temperature quenching at a temperature of 650℃ for 100 minutes, and then cooled to room temperature by immersion in water.

[0042] 6) Pickling: The high-temperature quenched wire blank is pickled to remove the surface oxide scale.

[0043] 7) Finished product extension: The pickled wire blank is extended into a finished product with a processing rate of 5.5%.

[0044] Example 2

[0045] The tellurium copper alloy comprises the following components by mass percentage: Te: 0.35wt%, P: 0.004wt%, Ce: 0.05%, with the balance being electrolytic copper.

[0046] 1) Batching, smelting and casting: The batching is carried out for smelting and casting. During the smelting and casting process, the surface of the melt is covered with charcoal with a thickness of 15cm, and the ingot is produced by electromagnetic stirring.

[0047] 2) Hot extrusion: The heated ingot is extruded in a horizontal extrusion press to obtain a billet. The extrusion ratio is 3:15, the extrusion temperature is 810℃, and the residual pressure accounts for 7% of the original length of the extruded ingot.

[0048] 3) Pickling: The hot-extruded billet is pickled to remove the surface oxide scale.

[0049] 4) Stretching: Cold deformation of the extruded billet by 38% processing amount.

[0050] 5) High-temperature quenching: The stretched wire blank is subjected to high-temperature quenching at a temperature of 750℃ for 50 minutes, and then cooled to room temperature by immersion in water.

[0051] 6) Pickling: The high-temperature quenched wire blank is pickled to remove the surface oxide scale.

[0052] 7) Finished product extension: The pickled wire blank is extended into a finished product with a processing rate of 9%.

[0053] Example 3

[0054] The tellurium copper alloy comprises the following components by mass percentage: Te: 0.31 wt%, P: 0.005 wt%, Y: 0.03%, Ce: 0.03%, with the balance being electrolytic copper.

[0055] 1) Batching, smelting and casting: The batching is carried out for smelting and casting. During the smelting and casting process, the surface of the melt is covered with charcoal with a thickness of 20cm, and the ingot is produced by electromagnetic stirring.

[0056] 2) Hot extrusion: The heated ingot is extruded in a horizontal extrusion press to obtain a billet. The extrusion ratio is 330, the extrusion temperature is 780℃, and the residual pressure accounts for 14% of the original length of the extruded ingot.

[0057] 3) Pickling: The hot-extruded billet is pickled to remove the surface oxide scale.

[0058] 4) Stretching: Cold deformation of the extruded billet by 45% processing amount.

[0059] 5) High-temperature quenching: The stretched wire blank is subjected to high-temperature quenching at a temperature of 780℃ for 30 minutes, and then cooled to room temperature by immersion in water.

[0060] 6) Pickling: The high-temperature quenched wire blank is pickled to remove the surface oxide scale.

[0061] 7) Finished product extension: The pickled wire blank is extended into a finished product with a processing rate of 14%.

[0062] Example 4

[0063] The tellurium copper alloy composition includes the following components by mass percentage: Te ingot: 0.22wt%, P: 0.002wt%, Y: 0.02%, Ce: 0.03%, with the balance being electrolytic copper.

[0064] 1) Batching, smelting and casting: The batching is carried out for smelting and casting. During the smelting and casting process, the surface of the melt is covered with charcoal with a thickness of 15cm, and the ingot is produced by electromagnetic stirring.

[0065] 2) Hot extrusion: The heated ingot is extruded in a horizontal extrusion press to obtain a billet. The extrusion ratio is 790, the extrusion temperature is 880℃, and the residual pressure accounts for 14% of the original length of the extruded ingot.

[0066] 3) Pickling: The hot-extruded billet is pickled to remove the surface oxide scale.

[0067] 4) Stretching: Cold deformation of the extruded billet by 35% processing amount.

[0068] 5) High-temperature quenching: The stretched wire blank is subjected to high-temperature quenching at a temperature of 680℃ for 60 minutes, and then cooled to room temperature by immersion in water.

[0069] 6) Pickling: The high-temperature quenched wire blank is pickled to remove the surface oxide scale.

[0070] 7) Finished product extension: The pickled wire blank is extended into a finished product with a processing rate of 8%.

[0071] Comparative Example 1

[0072] The tellurium copper alloy composition includes the following components by mass percentage: Te: 0.45wt%, with the balance being electrolytic copper.

[0073] 1) Batching, smelting and casting: The batching is carried out for smelting and casting. During the smelting and casting process, the surface of the melt is covered with charcoal with a thickness of 15cm, and the ingot is produced by electromagnetic stirring.

[0074] 2) Hot extrusion: The heated ingot is extruded in a horizontal extrusion press to obtain a billet. The extrusion ratio is 3:15, the extrusion temperature is 810℃, and the residual pressure accounts for 7% of the original length of the extruded ingot.

[0075] 3) Pickling: The hot-extruded billet is pickled to remove the surface oxide scale.

[0076] 4) Stretching: Cold deformation of the extruded billet by 38% processing amount.

[0077] 5) High-temperature quenching: The stretched wire blank is subjected to high-temperature quenching at a temperature of 750℃ for 50 minutes, and then cooled to room temperature by immersion in water.

[0078] 6) Pickling: The high-temperature quenched wire blank is pickled to remove the surface oxide scale.

[0079] 7) Finished product extension: The pickled wire blank is extended into a finished product with a processing rate of 9%.

[0080] Comparative Example 2

[0081] The tellurium copper alloy comprises the following components by mass percentage: Te: 0.25wt%, P: 0.004wt%, Y: 0.04%, with the balance being electrolytic copper.

[0082] 1) Batching, smelting and casting: The batching is carried out for smelting and casting. During the smelting and casting process, the surface of the melt is covered with charcoal with a thickness of 5cm, and the ingots are produced by continuous casting.

[0083] 2) Hot extrusion: The heated ingot is extruded in a horizontal extrusion press to obtain a billet. The extrusion ratio is 180, the extrusion temperature is 630℃, and the residual pressure accounts for 4% of the original length of the extruded ingot.

[0084] 3) Pickling: The hot-extruded billet is pickled to remove the surface oxide scale.

[0085] 4) Finished product extension: The pickled wire blank is extended into a finished product with a processing rate of 4.5%.

[0086] Comparative Example 3

[0087] The tellurium copper alloy comprises the following components by weight percentage: Te: 0.45wt%, P: 0.01wt%, Ce: 0.01%, with the balance being electrolytic copper.

[0088] 1) Batching, smelting and casting: The batching is carried out for smelting and casting. During the smelting and casting process, the surface of the melt is covered with charcoal with a thickness of 5cm, and the ingots are produced by continuous casting.

[0089] 2) Hot extrusion: The heated ingot is extruded in a horizontal extrusion press to obtain a billet. The extrusion ratio is 180, the extrusion temperature is 880℃, and the residual pressure accounts for 3% of the original length of the extruded ingot.

[0090] 3) Pickling: The hot-extruded billet is pickled to remove the surface oxide scale.

[0091] 4) Stretching: Cold deformation of the extruded billet by 18% processing amount.

[0092] 5) High-temperature quenching: The stretched wire blank is subjected to high-temperature quenching at a temperature of 800℃ for 150 minutes, and then cooled to room temperature by immersion in water.

[0093] 6) Pickling: The high-temperature quenched wire blank is pickled to remove the surface oxide scale.

[0094] 7) Finished product extension: The pickled wire blank is extended into a finished product with a processing rate of 17%.

[0095] Comparative Example 4

[0096] The tellurium copper alloy comprises the following components by weight percentage: Te: 0.15wt%, P: 0.01wt%, Ce: 0.01%, with the balance being electrolytic copper.

[0097] 1) Batching, smelting and casting: The batching is carried out for smelting and casting. During the smelting and casting process, the surface of the melt is covered with charcoal with a thickness of 8cm, and the ingots are produced by continuous casting.

[0098] 2) Hot extrusion: The heated ingot is extruded in a horizontal extrusion press to obtain a billet. The extrusion ratio is 250, the extrusion temperature is 680°C, and the residual pressure accounts for 3% of the original length of the extruded ingot.

[0099] 3) Pickling: The hot-extruded billet is pickled to remove the surface oxide scale.

[0100] 4) Stretching: Cold deformation of the extruded billet by 18% processing amount.

[0101] 5) Annealing: Anneal the stretched wire blank at a holding temperature of 580℃ for 160 minutes.

[0102] 6) Pickling: Pickling the annealed wire blanks to remove the surface oxide scale.

[0103] 7) Finished product extension: The pickled wire blank is extended into a finished product with a processing rate of 10%.

[0104] The samples prepared in the comparative and example cases were subjected to tests for conductivity, oxygen content, tensile strength, metallography, etc.

[0105] The conductivity was measured in accordance with GB / T351-2019 "Metallic Materials - Test Method for Resistivity".

[0106] The oxygen content was measured in accordance with GB-T14265-2017 "General Rules for Analysis of Hydrogen, Oxygen, Nitrogen, Carbon and Sulfur in Metallic Materials".

[0107] Tensile strength and elongation were measured in accordance with GT / T 34505-2017 "Tension Test Method for Copper and Copper Alloy Materials at Room Temperature".

[0108] 1mm 2 The amount of Cu2Te phase inside was obtained by analyzing a 500x metallographic image using Pro-Image software.

[0109] The average grain diameter was measured according to YS-T347-2020 "Method for Determination of Average Grain Size of Copper and Copper Alloys".

[0110] Arc burn resistance test: The mass difference before and after 500 arc burns is used as the measure. The test conditions are as follows: ambient temperature 23℃, on / off ratio 0.05s:20s, DC voltage 750V, current 120A.

[0111] Helium leak detection test: The test is conducted using the negative pressure helium injection method.

[0112] As shown in Table 1, and as shown in Table 2, Figure 1 and Figure 2 As shown, the tellurium copper alloys obtained in Examples 1-4 of this invention have a conductivity >90% IACS, an oxygen content <10ppm, a tensile strength >230MPa, an elongation >25%, and a 1mm elongation of [missing information]. 2 The number of Cu2Te phases is 7,000-10,000, the average grain size is 10-20 μm, the arc burn-off loss after 500 cycles is less than 5 mg, and the failure rate of helium leak detection in the high voltage DC relay prepared is less than 50 ppm.

[0113] Table 1. Performance comparison of the materials in the examples and comparative examples.

[0114]

[0115]

Claims

1. A tellurium copper alloy, characterized in that: The invention comprises Cu, Te, doping elements and inevitable impurities, the total mass percentage of all elements is 100%, wherein Te is 0.2-0.4wt%, the doping elements include P: 0.002-0.006wt%, X: 0.02-0.06%, X is Y and / or Ce; The structure of the tellurium copper alloy includes Cu2Te phase, and the number distribution of the Cu2Te phase is 7000-10000 / mm 2 .

2. The tellurium copper alloy according to claim 1, characterized in that: The average grain size of the tellurium copper alloy is 10-20 μm.

3. The tellurium copper alloy according to claim 1, characterized in that: The electrical conductivity of the tellurium copper alloy is greater than 90% IACS, the oxygen content is less than 10 ppm, the tensile strength is greater than 230 MPa, the elongation is greater than 25%, and the arc burnout after 500 times is less than 5 mg.

4. A method for preparing a tellurium copper alloy according to any one of claims 1 to 3, characterized in that: The process flow of the preparation method is: melting and casting of ingredients → hot extrusion → pickling → stretching → high temperature quenching → pickling → finished product stretching; Wherein, the ingredients are prepared according to the percentage of each component of the tellurium-copper alloy as described in any one of claims 1 to 3; Wherein, the temperature of the high temperature quenching is 620-780°C, and the holding time is 30-120 minutes.

5. The method for preparing a tellurium copper alloy according to claim 4, characterized in that: The high temperature quenching is performed by water cooling.

6. The method for preparing a tellurium copper alloy according to claim 4, characterized in that: During the melting and casting process, the surface of the melt is covered with charcoal, and the thickness of the charcoal covering is 10 to 20 cm.

7. The method for preparing a tellurium copper alloy according to claim 4, characterized in that: In the melting and casting process, electromagnetic stirring is used to stir the melt.

8. The method for preparing a tellurium copper alloy according to claim 4, characterized in that: The average grain diameter of the ingot obtained by melting and casting the ingredients is less than 500 μm.

9. The method for preparing a tellurium copper alloy according to claim 4, characterized in that: In the melting and casting process, the extrusion ratio of the hot extrusion is 200-800, the extrusion temperature is 650-900° C., and the pressure surplus control amount of the hot extrusion accounts for 5-15% of the original length of the extruded ingot.

10. Application of the tellurium copper alloy according to any one of claims 1 to 3 in a high voltage DC relay, characterized in that: The helium leak detection failure rate of the high voltage DC relay is less than 50 ppm.

Citation Information

Patent Citations

  • Preparation method for tellurium-copper alloy material

    CN110284024A

  • Tellurium-copper alloy strip and preparation method thereof

    CN116083749A